ASSESSMENT OF GENETIC VARIABILITY IN TEST CROSS HYBRIDS OF MAIZE (Zea mays L.) - T. RAMYA VARDHINI, A. PRASANNA RAJESH , I. SUDHIR KUMAR* and D. RAMESH (The Journal of Research ANGRAU, 2023)
Estimation of genetic parameters viz., genetic variability, heritability and genetic advance as percent ofmean of a character helps in the selection of the breeding programme for the development of the particulartrait. Analysis of variance recorded highly significant differences for twelve characters among 54 test crosshybrids of maize except for protein content. The magnitude of PCV was higher than the GCV for all thecharacters studied indicating the role of environment in the expression of these traits. Higher estimates ofPCV and GCV were recorded by the trait grain yield (kg ha-1). The character grain yield (kg ha-1) also recordedhigh heritability associated with high genetic advance as per cent of mean indicating the role of additive geneaction, and hence, selection of this trait may be effective. Alternatively, the traits days to anthesis, days tosilking, ear length, ear girth, kernel rows per ear, and shelling percentage showed medium heritability withlower genetic gain indicating the predominance of non-additive gene action.